192 Abundance of rumen methanogens did not differ in cattle that differed in residual feed intake - Freetly, Harvey C (J Anim Sci, 2020)
Methane represents an energetic loss, and it has been proposed that its reduction may be associated with improved feed efficiency. Rumen methanogens produce most of the methane. Forty-nine crossbred heifers were individually fed a ration that consisted of 67.75% rolled corn, 20% wet distillers grain with solubles, 8% chopped alfalfa and 4.25% mineral/vitamin/rumensin mix for 84 d. Residual feed intake was the residual of the observed – predicted FI for the multivariate regression of FI on ADG and mid-metabolic BW for the population. Six heifers with the greatest RFI (1.75 ± 0.31 kg DM/d) and 6 with least RFI (-1.48 ± 0.31 kg DM/d) were selected. Rumen fluid was sampled from a tube passed through the mouth into the rumen. Rumen fluid was flash frozen in liquid N(2) and stored at -80°C. After the first collection, heifers with greater RFI were pair fed to the less RFI heifers and rumen fluid was sampled 5 wk later. DNA was isolated from the rumen fluid and primer sets targeting total methanogens, Methanomicrobiales, Methanobacteriales, Methanosarcina, Methanobacterium, Methanobrevibacter ruminantium + Mbb. Cuticularis, and Methanobrevibacter smithii + Mbb. wolinii + Mbb. thaueri + Mbb. gottschalkii + Mbb. Woesei were amplified with real-time quantitative PCR (qPCR). Standard curves were generated to quantify copy number. There were no differences in copy number for the interaction of RFI classifications and sample period for all primer sets (P > 0.18). There were no differences in (P > 0.15) in RFI classification for all qPCR primer sets. There were fewer copies for the Methanobrevibacter ruminantium + Mbb. Cuticularis qPCR for samples collected in the first week compared to the 5 wk sample (P = 0.03); however, there were no difference for collection week for the other qPCR assays (P > 0.16). USDA is an equal opportunity provider and employer.